Perawatan Diri Ibu Primipara Selama Periode Nifas - Jumiati Riskiyani Dwi Nandia; Anggorowati Anggorowati; Fatikhu Yatuni Asmara (Jurnal Keperawatan Silampari, 2021)
This study aims to describe how primiparous mothers perform self-care during the postpartum period. The method used is a literature review study by searching for several articles and journals through a search process from Pubmed, Proquest, Scopus Ebsco, and Google scholar. The results showed that many primiparous mothers needed self-care education to take care of themselves and their babies during the postpartum period. Self-care for each primiparous mother during childbirth is very different, one of which is due to the knowledge and age of the mother. Primiparous mothers are more likely to learn to understand themselves in terms of self-care during the puerperium than are multiparous who have had previous experiences. In conclusion, most primiparous mothers are still less able to do self-care because primiparous mothers have no experience caring for themselves and their babies, so they still tend to learn and try harder to adjust to their conditions. Keywords: Independence, Postpartum, Primipara